Saudi University Students’ Perceptions towards Language Learning via Blackboard During Covid-19 Pandemic: A Case Study of Department of Languages and Translation, Taibah University, Al-Ula Campus - Hezam, Abdulrahman Mokbel Mahyoub; Mahyoub, Rian Abdulrahman Moqbel (Advances in Social Sciences Research Journal, 2022)
This study investigates the use of Blackboard in teaching and learning English as a foreign language at the Department of Languages and Translation, Faculty of Science and Arts, Taibah University (TU) in Al-Ula, Saudi Arabia. It aims to investigate the efficiency of using Blackboard in EFL. The study tries to answer the following questions: What are the effects of using Blackboard in teaching and learning English as a foreign language on the development of language skills? What are the attitudes of EFL learners toward using Blackboard at Saudi EFL colleges? The descriptive research design used a quantitative instrument to accomplish the study's objectives; a survey questionnaire was used to investigate the attitudes of EFL BA college students towards the use of Blackboard in EFL. The findings of the study help educators assess the efficiency of using Blackboard in teaching English. The results show that students have a positive attitude towards Blackboard but still face difficulties adapting to online learning.